The Effect Of Work Life Balance On Improving Employee Performance - et. al., Shinta Oktafien, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to determine how much influence work life balance has on improving employee performance at PT Vegatyan Inti Prakasa. As for the population in this study are all employees who work in this company with the number of samples taken as much as the total population of 49 employees. The research method used is descriptive and verification research methods with processing techniques and data analysis in the form of simple linear regression analysis. Based on the results of data processing and analysis, it is known that work life balance has a significant effect on improving employee performance at PT. Vegatyan Inti Prakasa. Thus, it is known that if every employee who works has a balanced quality of life between work and life outside his / her job, then the work results shown by the employee can be even better